PENERAPAN BIOTEKNOLOGI PRODUK SUSU YOGURT DAN KEJU UNTUK MENINGKATKAN NILAI TAMBAH DAN DAYA SAING KELOMPOK TANI SUPRAH DI DUSUN SILEMBU BANJARNEGARA - Niko Siameva Uletika; Naofal Dhia Arkan; Radita Dwi Putera; Lasmedi Afuan; Mulki Indana Zulfa (Jurnal Abdi Insani, 2025)
This dedication aims to analyze the implementation of digital transformation in Nagari Bukit Buai Tapan through the integration of regional profiles, management of organic compost, and the use of family medicinal plants (Toga) as an effort to support sustainable development. The methodology used includes socialization of programs to local stakeholders, training in nagari and community devices in the use of digital information systems, regional mapping with simple software, as well as direct practice of cultivating toga and making household compost. This program is implemented in a participatory manner by involving nagari devices, farmer groups, health cadres, youth, and beneficiary households. The results of this service indicate that the digital information system is successfully operated by the Nagari device to manage population data and local potential. The regional mapping produces administrative maps that are printed and installed in the Nagari office and are available in digital format. More than 20 households planted toga, including ginger, turmeric, and lemongrass, while three units of household composter began to be actively used with kitchen waste and EM4. Analysis shows a significant increase in public knowledge related to herbal -based health and environmentally friendly waste management. The discussion confirms that the integration of digitalization, organic compost, and toga not only strengthens data-based governance, but also encourages food independence, health, and preservation of local wisdom. This finding implies that holistic digital nagari transformation models can be an effective strategy to strengthen governance, improve welfare, and support sustainable development. This research contributes conceptual and practical to the development of local village based on local wisdom that can be replicated in other nagari.